Design and development of hybrid energy generator (photovoltaics) with solar tracker - Mohiuddin, A. K. M.; Sabarudin, Mohamad Syabil; Khan, Ahsan Ali; Ihsan, Sany Izan (IOP Publishing, 2017)
This paper is the outcome of a small scale hybrid energy generator (hydro and photovoltaic) project. It contains the photovoltaics part of the project. The demand of energy resources is increasing day by day. That is why people nowadays tend to move on and changes their energy usage from using fossil fuels to a cleaner and green energy like hydro energy, solar energy etc. Nevertheless, energy is hard to come by for people who live in remote areas and also campsites in the remote areas which need continuous energy sources to power the facilities. Thus, the purpose of this project is to design and develop a small scale hybrid energy generator to help people that are in need of power. This main objective of this project is to develop and analyze the effectiveness of solar trackers in order to increase the electricity generation from solar energy. Software like Solidworks and Arduino is used to sketch and construct the design and also to program the microcontroller respectively. Experimental results show the effectiveness of the designed solar tracker sytem.